ANALISISI BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP INTENSITAS KERJA DAN KONTRIBUSI PENDAPATAN ASISTEN RUMAH TANGGA - I Made Krisnaryana; I Gusti Wayan Murjana Yasa (PIRAMIDA, 2018)
Respondents in this study are married women who work as a household assistant. Objects in the study includeage, wages, education, the number of dependents, work intensity and income contribution. The sample in this studyamounted to 96 respondents. In this research the method used to collect information and data that is observation,interview and depth interview. Data analysis technique used is path analysis / path analysis and test sobel to analyzeindirect influence through intervening variable. The result of the research shows that age, wage, and dependenthave direct and significant influence to work intensity, and age, wage, dependent amount and amount of husband’sincome have a direct and significant effect to income contribution, and age, wage, and dependent influence indirectlyThrough work intensity variables on income contribution of married women who work as household assistants